Examining the link between coach-athlete relationship and athlete burnout among college soccer players: the mediating role of training satisfaction - Jiahao, Liu; Jing, Li (Frontiers in Psychology, 2024)
Purpose: Athlete burnout is an essential adverse factor that usually decreases athletes’ sports performance and reduces their passion for entire athletic career development. The present study examined the association of coach-athlete relationship, training satisfaction, and athlete burnout, and then explored the training satisfaction as a mediating role of the effect of coach-athlete relationship on athlete burnout among college soccer players. Methods: Took soccer players from seven Chinese higher education institutions in China as the object, selected the subjects by stratified random sampling, and finally obtained 218 samples. The Coach-Athlete Relationship Scale, Training Satisfaction Scale, and Athlete Burnout Questionnaire were used to measure the basic information of participants respectively. Pearson’s product-moment correlation analysis, linear regression analysis, and bootstrap method were conducted to analyze the collected data set. Results: The results showed that 1) there was a significant correlation relationship between coach-athlete relationship, training satisfaction, and athlete burnout. 2) coach-athlete relationship and training satisfaction significantly negatively affected athlete burnout (β = -0.39, p<0.001; β =- 0.29, p < 0.001). 3) training satisfaction has a significantly mediating effect on the relationship between coach-athlete relationship and athlete burnout (β = -0.15, p < 0.001, ES = 0.28). Conclusion: Coach-athlete relationship can not only directly negative impact on athlete burnout but can also negatively influence athlete burnout through the mediating effect of training satisfaction. Therefore. We suggest the following to alleviate athlete burnout: on one hand, coaches can provide more communication opportunities for athletes to improve the coach-athlete relationship. On the other hand, teams can enhance training satisfaction by building team culture.